A Tactile-based Brain Computer Interface P300 Paradigm Using Vibration Frequency and Spatial Location - Han, Xiangke; Niu, Jianye; Guo, Shijie (Journal of medical and biological engineering, 2020)
Purpose Visual based brain-computer interface (BCI) has been widely investigated for the severely disabled patients. However, this modality is not applicable to the persons who have lost their visual function. This study aims to develop an alternative BCI using tactile stimuli only. Methods An event-related potential (ERP) based BCI applying vibrotactile stimuli was proposed. It featured a combination of frequency and spatial information as a cue for binary choices. Two identical mechanical vibrotactile tactors were tied to each index finger of the two hands of a subject, to provide vibrotactile stimuli at various frequencies and constitute a three-stimulus oddball paradigm with one attended stimulus, one ignored stimulus and one disturbance stimulus. Ten healthy subjects participated in the experiments, and the classification of P300 signals was conducted by a stepwise linear discriminate analysis algorithm. Results Significant P300 components were evoked at approximately 360 ms after the onset of the target stimuli for each subject, and an average classification accuracy of 79% was achieved. Conclusions This work demonstrates the feasibility of employing vibrotactile stimuli to build an ERP based BCI. The patients without a functional visual system could benefit from the presented paradigm.